The impact of social media use towards negative emotion and suicidal tendency among students: a systematic review / Peng Yifan and Wardatul Hayat Adnan - Yifan, Peng; Adnan, Wardatul Hayat (Universiti Teknologi MARA, 2021)
The fourth industrial revolution has brought the world into the digital age. The rapid growth of communication equipment and network infrastructure has brought the world closer. The speed of information dissemination has been greatly improved, the scope of dissemination has been expanded, and the unparalleled timeliness and convenient accessibility of social media enable users to exert their influence freely. Therefore, some negative information or emotions spread rapidly, affecting users’ emotions and attitudes. The purpose of this study is to find out the current evidence that the use of social media has an impact on the negative emotions and attitudes of students. Adapting PRISMA publication standard for systematic review, the study systematically searched articles in four databases: Web of Science, Google Scholar, Scopus and ProQuest. The focus of this study is to use social media, students’ negative emotions and suicide attitudes to investigate the use of social media, negative emotions and even suicide attempts by young students. The conclusion shows that students’ use of social media may increase the risk of negative emotions such as depression and even suicidal behaviour.